Synthesis, characterization, Hirshfeld surface, cytotoxicity, DNA damage and cell cycle arrest studies of N, N-diphenyl-N `-(biphenyl-4-carbonyl/4-chlorobenzoyl) thiocarbamides - Pandey, Sunil K.; Pratap, Seema; Rai, Sunil K.; Marverti, Gaetano; Kaur, Manpreet; Jasinski, Jerry P. (Journal of Molecular Structure, 2019)
The condensation reaction of biphenyl-4-carbonyl isothiocyanate/4-chlorobenzoyl isothiocyanate with diphenylamine yielded two new compounds; N-diphenyl-N'-(biphenyl-4-carbonyl) thiocarbamide (1) and N, N-diphenyl-N'-(4-chlorobenzoyl) thiocarbamide (2). Structure of the compounds were determined by analytical, spectroscopic (UV-Visible, FT-IR, H-1, & C-13 NMR), powder and single-crystal X-ray diffraction methods. Hirshfeld surface analysis and their associated two dimensional fingerprint plots of compounds were used as theoretical approach to assess driving force for crystal structure formation via the intermolecular interactions in their crystal lattices. The compounds were screened for their in vitro cytotoxicity activity against a panel of five human cancer cell lines namely; cervical (2008 and C13*) and ovarian carcinoma (A2780, A2780/CP and IGROV-1). Both the compounds exhibited promising activity against cervical and IGROV-1 cancer cells whereas for the other two cell lines appreciable activities were observed. The cell cycle arrest at G(0)/G(1) phase is supported by the DNA damage and apoptosis studies of the compounds against 2008, C13* and IGROV-1 cell lines. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: DNA damage and cell cycle arrest; Hirshfeld surface analysis; In vitro cytotoxicity; Thiocarbamide; X-ray crystal structure